2022
DOI: 10.1002/glia.24300
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 dysfunction in oligodendrocytes contributes to the pathogenesis of multiple sclerosis

Abstract: Oligodendrocyte (OL) damage and death are prominent features of multiple sclerosis (MS) pathology, yet mechanisms contributing to OL loss are incompletely understood. Dysfunctional RNA binding proteins (RBPs), hallmarked by nucleocytoplasmic mislocalization and altered expression, have been shown to result in cell loss in neurologic diseases, including in MS. Since we previously observed that the RBP heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) was dysfunctional in neurons in MS, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…In this study, we described for the first time the transcripts associated with hnRNP A2 in oligodendrocytes. In particular, in agreement with data described for hnRNP A1 (73), hnRNP A2 regulated genes associated with RNA biology, involved in RNA metabolism, processing and splicing, biogenesis of ribonucleoprotein complexes and translation regulation. Intriguingly, we observed that Aβ upregulates hnRNP A2 and disrupts its associated transcripts, leading to a weakening of interactions with over 50% of total mRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we described for the first time the transcripts associated with hnRNP A2 in oligodendrocytes. In particular, in agreement with data described for hnRNP A1 (73), hnRNP A2 regulated genes associated with RNA biology, involved in RNA metabolism, processing and splicing, biogenesis of ribonucleoprotein complexes and translation regulation. Intriguingly, we observed that Aβ upregulates hnRNP A2 and disrupts its associated transcripts, leading to a weakening of interactions with over 50% of total mRNAs.…”
Section: Discussionsupporting
confidence: 90%
“…Alterations in RBP expression levels and function have been associated with neurological disorders (e.g. HNRNPA1 [ 45 ], MATR3 [ 46 , 47 ], TIA1 [ 48 ], and TARDBP [ 49 ] and brain tumour development (e.g. Musashi1 [ 8 , 50 , 51 ], SERBP1 [ 11 ], PTB [ 12 ] and HuR [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA binding proteins (RBPs) modulate numerous steps in gene expression and are particularly relevant in the nervous system (neurogenesis and brain development (Popper et al, 2021; Prashad and Gopal, 2021)), where they orchestrate changes in splicing, translation, and mRNA decay. Alterations in RBP expression levels and function have been associated with neurological disorders (e. g., HNRNPA1 (Jahanbazi Jahan-Abad et al, 2022), MATR3 (Johnson et al, 2014), TIA1 (Mackenzie et al, 2017), and TARDBP (Valdmanis et al, 2009)) and brain tumor development (e.g., Musashi1 (Toda et al, 2001; Galante et al, 2009; Velasco et al, 2019; Baroni et al, 2021a), SERBP1(Correa et al, 2016), PTB (McCutcheon et al, 2004) and HuR (Filippova et al, 2011; Guha et al, 2022a)). Modulation of their expression or target genes with specific inhibitors has started to be explored therapeutically (Hong, 2017).…”
Section: Discussionmentioning
confidence: 99%